2008
DOI: 10.1111/j.1538-7836.2007.02808.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen synthesized by cancer cells augments the proliferative effect of fibroblast growth factor‐2 (FGF‐2)

Abstract: These data indicate that endogenously synthesized fibrinogen promotes the growth of lung and prostate cancer cells through interaction with FGF-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 47 publications
6
150
0
3
Order By: Relevance
“…In line with previous publications (Wernert et al, 2007;Sahni et al, 2008), we observed that FGF-2 treatment of prostate cancer cells DU145 and PC3 stimulates proliferation and migration, respectively, as shown by cell growth evaluation and scratch-wound assay ( Supplementary Figures 2c and d). By luciferase assay, we demonstrated FGF-2 and FGFR1 as new direct targets of miR-15 and miR-16 (Supplementary Figure 2e).…”
Section: Fgf-2 and Fgfr1 Are New Targets Of Mir-15 And Mir-16supporting
confidence: 92%
“…In line with previous publications (Wernert et al, 2007;Sahni et al, 2008), we observed that FGF-2 treatment of prostate cancer cells DU145 and PC3 stimulates proliferation and migration, respectively, as shown by cell growth evaluation and scratch-wound assay ( Supplementary Figures 2c and d). By luciferase assay, we demonstrated FGF-2 and FGFR1 as new direct targets of miR-15 and miR-16 (Supplementary Figure 2e).…”
Section: Fgf-2 and Fgfr1 Are New Targets Of Mir-15 And Mir-16supporting
confidence: 92%
“…We have shown that lung, prostate and breast cancer epithelial cells synthesize and secrete Fg that enhances FGF-2-mediated cell proliferation, assembles into extracellular matrices and binds to cancer cell surfaces. 2,14,[32][33][34][35][36][37] In addition, others have demonstrated Fg production in adenocarcinoma cell lines of cervical 15 and intestinal 16 origin. Recent expression array profiling studies have confirmed that the Fg genes are expressed in breast 17 and lung carcinomas 18,19 isolated from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both MoAbs T2G1 (anti-FgBb [15][16][17][18][19][20][21] ) and BV9 (anti-VE-cadherin EC3-EC4), but not MoAb 18C6 (anti-FPB Bb [1][2][3][4][5][6][7][8][9][10][11][12][13][14], partially inhibited Fg-induced FITCDextran Flux, implicating VE-cadherin and Fg-b in mechanisms of Fg-induced EC permeability. Fg is capable of inducing permeability of different types of barrier EC, as Fg also induced permeability of a microvascular EC barrier, whereas it did not induce permeability of an epithelial cell barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations